Single and Repeated Use of the Emergency Department for Chlamydia and Gonorrhea Care. Issue 1 (January 2020) - Bergquist, Eleanor Peters; Trolard, Anne; Zhao, Yueming; Kuhlmann, Anne Sebert; Loux, Travis; Liang, Stephen Y.; Stoner, Bradley P.; Reno, Hilary
Abstract : Objective: Chlamydia and gonorrhea infection rates are rising in the United States, and the emergency department (ED) is increasingly a site where individuals seek care for these infections, sometimes more than once. This article investigates how individuals who use the ED more than once and receive chlamydia and gonorrhea care differ from individuals who are single users of the ED, as well as characteristics associated with being a repeat user of the ED. Methods: We analyzed 46, 964 visits made by individuals who attended 1 of 4 EDs from January 1, 2010, to May 31, 2016, and received a test for chlamydia and gonorrhea infection. We used negative binomial regression to test the ability of age, sex, race, infection status, and insurance status to predict number of visits. Results: Individuals who used the ED more than once and received chlamydia and gonorrhea care were at their first visit more likely to be younger (incident rate ratio [IRR], 0.98; 95% confidence interval [CI], 0.97–0.98 per year) nonpregnant female (IRR, 1.23; 95% CI, 1.06–1.42), black (IRR, 1.27; 95% CI, 1.04–1.57), and have no or public insurance compared with single users of the ED. Discussions: Individuals likely to make multiple visits to the ED and receive chlamydia and gonorrhea care may be identifiable on their first visit and potentially directed elsewhere during subsequent visits for more comprehensive and potentially less expensive sexually transmitted disease care. Abstract : A study of emergency department patients revealed that individuals making multiple visits and receiving chlamydia/gonorrhea care may be identified and directed elsewhere for potentially less expensive sexually transmitted disease care.